Pengaruh Likuiditas, Komite Audit, dan Ukuran Perusahaan Terhadap Kinerja Keuangan (Studi Empiris pada Perusahaan Manufaktur Sektor Consumer Goods terdaftar di BEI Periode 2017 - 2019) - Novrizal Syamra; Adam Zakaria; Ati Sumiati (LPPM Universitas Negeri Jakarta, 2021)
This study is to examine the effect of liquidity, audit committee, and company size on the financial performance of manufacturing companies in the consumer goods sector on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The method used in research is quantitative. Secondary data obtained from www.idx.co.id. The use of this analysis is to use multiple linear regression to analyze the results on the independent variable to the dependent. The population of consumer goods is 60 companies and the research sample is 37 companies, selected using the purpose sampling method. This study gives the result that liquidity has no effect on financial performance. then the audit committee variable has a significant effect on financial performance. the next variable company size has no effect on financial performance. However, simultaneously on the liquidity variable, the audit committee and also the size of the company have an influence on the financial performance of manufacturing companies in the consumer goods sector. The result of the coefficient of determination is 8% while the remaining 92% is explained by other variables outside of this study.